Rancang Bangun Sistem Informasi Pengelolaan Kas RT/RW Berbasis Web di RW 05 Muncul - Hafizh Rafid Hidayat; Farizi Ilham; Muhammad Faiz; Alfitra Ersa Ramadhan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The management of cash funds within the scope of Rukun Warga (RW) 05, Muncul Village, is currently still conducted conventionally through physical ledger records. This method triggers various operational obstacles, such as a high risk of human error in data recapitulation, delays in searching transaction histories, and a lack of transparency in financial reporting to residents. This study aims to design and develop a web-based RT/RW cash management and reporting information system as a digital solution for financial administration. The system development applies the Waterfall model, implementing the Laravel framework and the Filament admin panel on the backend, with MySQL as the database management system. The final result of this research is a web platform capable of automating the recording of residents' monthly dues, managing officers' salary slips, and presenting cash reports in real-time and transparently. The system implementation successfully increases the efficiency of financial data processing time and minimizes the risk of manipulation or loss of recorded data.